2009
DOI: 10.1038/labinvest.2008.114
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the renal–skeletal–gut axis that controls phosphate homeostasis

Abstract: Under physiological conditions, homeostasis of inorganic phosphate (Pi) is tightly controlled by a network of increasingly more complex interactions and direct or indirect feedback loops among classical players, such as vitamin D (1,25(OH)2D3), parathyroid hormone (PTH), intestinal and renal phosphate transporters, and the recently described phosphatonins and minhibins. A series of checks and balances offsets the effects of 1,25(OH)2D3 and PTH to enable fine-tuning of intestinal and renal Pi absorptive capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 81 publications
(80 reference statements)
2
36
0
6
Order By: Relevance
“…Our study shows a significant decrease (Ϫ97%; P Ͻ 0.05) in NPT2A renal phosphate transporter mRNA expression is likely responsible for the lowered serum P i . However, altered NPT2c expression may also be involved since both NPT2a and NPT2c renal phosphate transporters are decreased in several familial and oncogenic hypophosphatemic bone mineralization disorders including HYP, ADHR, ARHR, and TIO (27,45,49,59). As reported previously, we found increased serum ASARM peptides in mice with HYP relative to normal mice (2,9,31,37,48,66).…”
Section: Discussionsupporting
confidence: 83%
“…Our study shows a significant decrease (Ϫ97%; P Ͻ 0.05) in NPT2A renal phosphate transporter mRNA expression is likely responsible for the lowered serum P i . However, altered NPT2c expression may also be involved since both NPT2a and NPT2c renal phosphate transporters are decreased in several familial and oncogenic hypophosphatemic bone mineralization disorders including HYP, ADHR, ARHR, and TIO (27,45,49,59). As reported previously, we found increased serum ASARM peptides in mice with HYP relative to normal mice (2,9,31,37,48,66).…”
Section: Discussionsupporting
confidence: 83%
“…Our group's findings related to osteoblast/osteocytespecific Phex gene also support at least partial contribution of defective bone formation in colitis. Phex is a critical regulator of systemic P i homeostasis (52), with an intrinsic role in osteoblast mineralization. Immortalized osteoblasts from Phexdeficient Hyp mice fail to mineralize under permissive conditions in vitro (109).…”
Section: Bone Formation Vs Resorption In Animal Models Of Ibdmentioning
confidence: 99%
“…Phex inactivation was postulated to indirectly affect the kidney through bone-released, phosphaturic factors known as phosphatonins. Fibroblast growth factor 23 (FGF23) was one of the leading phosphatonin candidates due to its potent negative effects on renal phosphate reabsorption and its highly elevated expression in X-linked hypophosphatemic ricket patients (6). Although initial studies seemed to confirm this mechanism (7), it was later shown that Phex mutations lead to increased FGF23 expression rather than processing (8), and that FGF23 is cleaved by subtilisin-like proprotein convertases and not PHEX (9).…”
mentioning
confidence: 99%